The impact of psychological attachment on the relationship between periodontal health and dental fear in patients with versus without psoriasis: a questionnaire-based, cross-sectional study - Christian Graetz; Sirka Woeste; Ullrich Mrowietz; Johannes C. Ehrenthal (BMC, 2021)
Abstract Background While there is increasing evidence for the relevance of psychosocial variables such as dental fear or psychological attachment in dentistry, much less is known about the mechanisms that determine the strength of those associations. One potential moderator is the occurrence of a comorbid chronic disease such as psoriasis, which is linked to relevant disease parameters such as periodontal inflammation. The aim of the study was to test a moderation model of the relationship between dental fear, psychological attachment and psoriasis on periodontal health. Methods A total of 201 patients (100 with psoriasis, 101 without psoriasis) were included in a questionnaire-based, cross-sectional study. Dental status was measured with the Community Periodontal Index (CPI), dental fear was measured with the Hierarchical Anxiety Questionnaire (HAQ), and psychological attachment was measured with the Relationship Questionnaire (RQ). In addition to the examination of main effects, bootstrapping-based analyses were conducted to test the moderating influence of psychological attachment on the association between CPI and dental fear, gain moderated by group (with vs. without psoriasis). Results Controlling for several covariates, higher CPI scores were associated with higher levels of dental fear only in individuals without psoriasis under conditions of higher levels of psychological attachment anxiety and lower levels of attachment avoidance. Conclusion In individuals without psoriasis, psychological attachment can moderate the association between periodontal health and dental fear. This may provide a useful framework for reducing dental fear through interventions on the level of the dentist-patient relationship.